Aging Impairs Endocytic Capacity Of Splenic Dendritic Cells From Dark Agouti Rats And Alters Their Response To TLR4 Stimulation - Biljana BUFAN (Sciendo, 2015)
The study was undertaken considering: i) that relative proportion of distinct subsets of splenic dendritic cells (DCs) is strain-specific and predictive for the susceptibility to autoimmune diseases; ii) age-related changes in endocytic, allostimulatory and polarizing capacity of splenic OX62+ DCs from Albino Oxford rats (relatively resistant to Th1/Th17-mediated diseases) and iii) strain specificities in age-related changes of mouse DCs. To ascertain whether there are strain specificities in age-related rat DC changes, we examined the influence of aging on OX62+ DCs from Dark Agouti (DA) rats prone to Th1/Th17-mediated autoimmune diseases. The study provided additional evidence that the predominance of CD4-cells within OX62+ DCs from young adult rats correlates with their susceptibility to Th1/Th17-mediated diseases. Consistently, lipopolysaccharide (LPS)-matured DCs from 3-month-old (young) rats exhibited Th1 driving force when co-cultured with allogeneic CD4+ T cells. This most likely reflected enhanced TNF-α and iNOS expression. Comparing with young rats, OX62+ DCs from 26-month-old (aged) rats showed: i) diminished endocytic capacity; ii) impaired ability to mature in vitro upon LPS stimulation (as indicated by lower MHC II, CD86 and CD40 surface expression), which is consistent with the increase in their IL-10 production, and iii) diminished allostimulatory capacity and loss of Th1-driving capacity in the mixed lymphocyte reaction. The latter, probably, reflected greater IL-10 production by LPS-stimulated DC from aged rats, as well as lower CD40 density on their surface. Overall, our findings suggest that aging might affect DA rat capability to mount an efficient Th1 immune response, and consequently susceptibility to Th1/Th17-mediated pathology.